Enantioselective total synthesis of putative dihydrorosefuran, a monoterpene with an unique 2,5-dihydrofuran structure - Torres-García, Irene; López-Martínez, Josefa L.; López-Domene, Rocío; Muñoz-Dorado, Manuel; Rodríguez-García, Ignacio; Álvarez-Corral, Miriam (Beilstein Journal of Organic Chemistry, 2022)
An original synthesis of the structure of dihydrorosefuran, a compound allegedly identified in Artemisia pallens and Tagetes mendocina, has been developed. The key steps in the five-step 36% overall yield synthesis are a CpTiIIICl2 mediated Barbier-type allenylation of a linear aldehyde and the formation of a 2,5-dihydrofuran scaffold through a Ag(I)-mediated cyclization. Neither of the reported spectral data for dihydrorosefuran match those of the synthetic product, suggesting that the isolated compound from Tagetes mendocina is in fact the natural product rosiridol, while the real structure of the product from Artemisia pallens remains unknown.
Keywords: Ag(I) cyclization; allenylation; CpTiCl2; 2,5-dihydrofurans; monoterpenes

(untitled) - Hellivan, P.-J. (Perfum. Flavor., 2011)

Artemisia - Kulkarni, R. N. (Artemisia pallens, 2002)

(untitled) - Subramoniam, A.; Pushpangadan, P.; Rajasekharan, S.; Evans, D. A.; Latha, P. G.; Valsaraj, R. (J. Ethnopharmacol., 1996)

(untitled) - Pavithra, K. S.; Annadurai, J.; Ragunathan, R. (J. Pharmacogn. Phytochem., 2018)

(untitled) - Mukherjee, A. A.; Kandhare, A. D.; Rojatkar, S. R.; Bodhankar, S. L. (Biomed. Pharmacother., 2017)

(untitled) - Chandra, A.; Misra, L. N.; Thakur, R. S. (Tetrahedron Lett., 1987)

(untitled) - Misra, L. N.; Chandra, A.; Thakur, R. S. (Phytochemistry, 1991)

(untitled) - Misra, L. N.; Chandra, A.; Thakur, R. S. (Phytochemistry, 1991)

(untitled) - Lima, B.; Agüero, M. B.; Zygadlo, J.; Tapia, A.; Solis, C.; Rojas De Arias, A.; Yaluff, G.; Zacchino, S.; Feresin, G. E.; Schmeda-Hirschmann, G. (J. Chil. Chem. Soc., 2009)

(untitled) - Nicolaou, K. C.; Snyder, S. A. (Angew. Chem., Int. Ed., 2005)

(untitled) - López-Martínez, J. L.; Torres-García, I.; Rodríguez-García, I.; Muñoz-Dorado, M.; Álvarez-Corral, M. (J. Org. Chem., 2019)

(untitled) - Torres‐García, I.; López‐Martínez, J. L.; Martínez‐Martínez, R.; Oltra, J. E.; Muñoz‐Dorado, M.; Rodríguez‐García, I.; Álvarez‐Corral, M. (Appl. Organomet. Chem., 2020)

(untitled) - Smith, A. B., III; Fukui, M.; Vaccaro, H. A.; Empfield, J. R. (J. Am. Chem. Soc., 1991)

(untitled) - Li, W.; Lin, Z.; Chen, L.; Tian, X.; Wang, Y.; Huang, S.-H.; Hong, R. (Tetrahedron Lett., 2016)

(untitled) - Hoye, T. R.; Jeffrey, C. S.; Shao, F. (Nat. Protoc., 2007)

(untitled) - Ali, Z.; Fronczek, F. R.; Khan, I. A. (Planta Med., 2008)

(untitled) - Yoshikawa, M.; Nakamura, S.; Li, X.; Matsuda, H. (Chem. Pharm. Bull., 2008)

(untitled) - Schöttner, E.; Simon, K.; Friedel, M.; Jones, P. G.; Lindel, T. (Tetrahedron Lett., 2008)

(untitled) - Frija, L. M. T.; Afonso, C. A. M. (Tetrahedron, 2012)